Investigating the interplay of loneliness, computer-mediated communication, online social capital, and well-being: insights from a COVID-19 lockdown study - Fahy, Megan; Barry, Marguerite (Frontiers in Digital Health, 2024)
IntroductionRecent studies have found that there is scope for communication technologies to increase online social capital. Although studies have linked online social capital and mental well-being, there is a need to identify the causal pathways within this relationship. This study explores the role of loneliness in the relationship between computer-mediated communication, online social capital and well-being.MethodsThe study used an online questionnaire and had 217 participants. William's 2006 scale was used to measure individuals’ online social capital, and structural equational modelling (SEM) was used to explore the relationship between computer-mediated communication, use, levels of loneliness, online social capital and well-being. This study was conducted remotely during the first COVID-19 lockdown in Ireland.ResultsHigh levels of online communication mitigated the otherwise negative effects of loneliness on well-being when online interaction fostered online social capital.ConclusionOverall, the proposed model offers qualified support for the continued analysis of technology-mediated communication as a potential source for building online social capital and improving the well-being of particular individuals with high levels of loneliness.